Neurobiologie in der Petrischale – Chancen und Herausforderungen - Kensington Potter Stephens; Zeynep Yentür; Simone Mayer (BIOspektrum, 2026)
Human neural organoids, 3-dimensional cultures derived from induced pluripotent stem cells, provide a platform to study brain development in a human-specific context. Using brain region-specific organoids, we modeled the rare neurological disorder PCH2a, examined the effects of prenatal exposure to an antiepileptic drug, and studied protein secretion during organoid differentiation. Taken together, neural organoids provide a versatile model system to study human brain development and its perturbations by genetic or environmental factors.

Conference Report: Cerebellar Development and Disease at Single-Cell Resolution - Lena M. Kutscher; Davide Aprile; N. Sumru Bayin; Esther B. E. Becker; Valentina Cerrato; Giacomo Turrini; Marion Coolen; Vincent Cantagrel; Béatrice C. Durand; Myron K. Evans II; Parthiv Haldipur; Kathleen J. Millen; et al. (The Cerebellum, 2025)

Unintended consequences of valuing the contributions of non-native species: misguided conservation initiatives in a megadiverse region - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Carlos Bernardo Mascarenhas Alves; Marlene Sofia Arcifa; Valter M. Azevedo-Santos; Marcelo Fulgêncio Guedes Brito; Pâmella Silva de Brito; Paula Maria Gênova de Castro Campanha; Fernando Rogério Carvalho; Gabriel Costa da Costa; Mario Alberto Cozzuol; Almir Manoel Cunico; et al. (Biodiversity and Conservation, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

First insights into Chinese reverse glass paintings gained by non-invasive spectroscopic analysis—tracing a cultural dialogue - Simon Steger; Diana Oesterle; Rupprecht Mayer; Oliver Hahn; Simone Bretz; Gisela Geiger (Archaeological and Anthropological Sciences, 2019)

Evaluation of the serum virome in calves persistently infected with Pestivirus A, presenting or not presenting mucosal disease - Matheus N. Weber; Samuel P. Cibulski; Simone Silveira; Franciele M. Siqueira; Ana Cristina S. Mósena; Mariana S. da Silva; Juliana C. Olegário; Ana Paula M. Varela; Thaís F. Teixeira; Matheus V. Bianchi; David Driemeier; Saulo P. Pavarini; et al. (Virus Genes, 2018)

Genomic and antigenic relationships between two ‘HoBi’-like strains and other members of the Pestivirus genus - Ana Cristina S. Mósena; Samuel P. Cibulski; Matheus N. Weber; Simone Silveira; Mariana S. Silva; Fabiana Q. Mayer; Paulo M. Roehe; Cláudio W. Canal (Archives of Virology, 2017)

Genomic characterization of a bovine viral diarrhea virus subtype 1i in Brazil - Ana Cristina S. Mósena; Matheus N. Weber; Samuel P. Cibulski; Simone Silveira; Mariana S. Silva; Fabiana Q. Mayer; Cláudio W. Canal (Archives of Virology, 2017)